2019
DOI: 10.1039/c9ra07130j
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of nitrogen-containing compounds on hydroxylated α-quartz surfaces

Abstract: Adsorption energies of different nitrogen-containing compounds on two hydroxylated (001) and (100) quartz surfaces are computed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The interaction between quartz surface and reagent adsorption is also reported, for example, various nitrogen-containing compounds on the hydroxylated α-quartz (001) and ( 100) surfaces are computed. Here the 2,4,6-trinitrotoluene (TNT) and 4dinitrotoluene (DNT) are preferably adsorbed on the (001) surface of α-quartz, while 3-nitro-1,2,4triazole-5-one (NTO) is located on both α-quartz surfaces (Tsendra et al, 2019). The DFT study revealed the depression mechanism of citric acid (CA) in sodium oleate flotation of Ca2+-activated quartz.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between quartz surface and reagent adsorption is also reported, for example, various nitrogen-containing compounds on the hydroxylated α-quartz (001) and ( 100) surfaces are computed. Here the 2,4,6-trinitrotoluene (TNT) and 4dinitrotoluene (DNT) are preferably adsorbed on the (001) surface of α-quartz, while 3-nitro-1,2,4triazole-5-one (NTO) is located on both α-quartz surfaces (Tsendra et al, 2019). The DFT study revealed the depression mechanism of citric acid (CA) in sodium oleate flotation of Ca2+-activated quartz.…”
Section: Introductionmentioning
confidence: 99%
“…Reagent interactions with quartz surfaces are also described, for example, the effects of various nitrogen-containing compounds on the hydroxylated α-quartz (001) and (100) surfaces. Wherein, 2,4,6-trinitrotoluene (TNT) and 2,4-dinitrotoluene (DNT) are preferably adsorbed on the α-quartz(001) surface, while 3-nitro-1,2,4-triazole-5-one (NTO) is found on both α-quartz surfaces (Tsendra et al 2019). When encountering macromolecules or large systems simulation, the dynamic statistical properties of mineral-water molecules (Li et al 2018;Yu et al 2021;Wang, Ren, and Yan 2021) interface interactions can be simulated and analyzed by the MD method.…”
Section: Introductionmentioning
confidence: 99%